What we talk about when we talk about ‘global mindset’: Managerial cognition in multinational corporations - Levy, Orly; Beechler, Schon; Taylor, Sully; Boyacigiller, Nakiye A (Journal of International Business Studies, 2007)
Recent developments in the global economy and in multinational corporations have placed significant emphasis on the cognitive orientations of managers, giving rise to a number of concepts such as ‘global mindset’ that are presumed to be associated with the effective management of multinational corporations. This paper reviews the literature on global mindset and clarifies some of the conceptual confusion surrounding the construct. We identify common themes across writers, suggesting that the majority of studies fall into one of three research perspectives: cultural, strategic, and multidimensional. We also identify two constructs from the social sciences – cosmopolitanism and cognitive complexity – that underlie the perspectives found in the literature. We then use these two constructs to develop an integrative theoretical framework of global mindset. We then provide a critical assessment of the field of global mindset and suggest directions for future theoretical and empirical research.